Systematic Literature Review Keberlangsungan Usaha Dalam UMKM : Tinjauan Sistematis - Sri Ayem; Reni Listyawati; Nanda Rachma Hernindya; Rifki Darmawan; Wito Febrian (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study reviews recently published scientific literature on business sustainability and Business Sustainability. Through a systematic review, we compiled and analyzed relevant literature to identify an in-depth understanding of business continuity and Business Sustainability. This research method involves identifying key articles through academic databases and preparing a literature synthesis. The main findings include a positive relationship between business continuity and thoughtful Business Sustainability in the context of business decision making and business planning. The research uses the SLR approach in journals published in 2018 and 2023, there are 50 indexed journals. Furthermore, business continuity and Business Sustainability are proven to be significant mediating factors in connecting business and business. The results of this analysis provide in-depth insight for stakeholders, including business practitioners, educators and policy makers, about the importance of developing financial literacy and how it can mediate changes in financial behavior that support business sustainability. Practical implications and recommendations for future research are also discussed. Thus, this research provides a solid conceptual foundation for a holistic understanding of the relationship between financial literacy, financial behavior and business sustainability.